Refining sonographic criteria for paediatric appendicitis: combined effects of age-based appendiceal size and secondary findings. Issue 12 (7th March 2022) - Neal, Jeffrey T; Monuteaux, Michael C; Rangel, Shawn J; Barnewolt, Carol E; Bachur, Richard G
Abstract : Objective: Appendiceal diameter is a primary sonographic determinant of paediatric appendicitis. We sought to determine if the diagnostic performance of outer appendiceal diameter differs based on age or with the addition of secondary sonographic findings. Methods: We retrospectively reviewed patients aged less than 19 years who presented to the Boston Children's Hospital ED and had an ultrasound (US) for the evaluation of appendicitis between November 2015 and October 2018. Our primary outcome was the presence of appendicitis. We analysed the cases to evaluate the optimal outer appendiceal diameter as a predictor for appendicitis stratified by age (<6, 6 to <11, 11 to <19 years), and with the addition of one or more secondary sonographic findings. Results: Overall, 945 patients met criteria for inclusion, of which 43.9% had appendicitis. Overall, appendiceal diameter as a continuous measure demonstrated excellent test performance across all age groups (area under the curve (AUC) >0.95) but was most predictive of appendicitis in the youngest age group (AUC=0.99 (0.98–1.00)). Although there was no significant difference in optimal diameter threshold between age groups, both 7- and 8-mm thresholds were more predictive than 6 mm across all groups (p<0.001). The addition of individual (particularly appendicolith or echogenic fat) or combinations of secondary sonographic findings increased the diagnostic value for appendicitis above diameter alone. Conclusions: Appendiceal diameter as a continuous measure was more predictive of appendicitis in the youngest group. Across all age groups, the optimal diameter threshold was 7 mm for the diagnosis of paediatric appendicitis. The addition of individual or combination secondary sonographic findings increases diagnostic performance.